Association of early acetaminophen administration with mortality in surgical intensive care patients: a retrospective cohort study - Li, Jiajing; Li, Yihao; Zhong, Min; Chen, Hanli; Wang, Ziyang; Wu, Jianwei; Shi, Yongyong (Frontiers in Pharmacology, 2025)
BackgroundAcetaminophen, a widely used analgesic, has drawn attention for its potential to reduce oxidative stress through inhibiting lipid peroxidation and scavenging free radicals. Emerging evidence indicates that early acetaminophen administration might improve survival outcomes in surgical intensive care unit (SICU) patients. This study aims to explore the relationship between early acetaminophen use and mortality in this patient population.MethodsWe conducted a retrospective cohort analysis of adult SICU patients using the Medical Information Mart for Intensive Care (MIMIC-IV) database, which contains data on patients admitted between 2008 and 2019. The intervention cohort received acetaminophen within 48 h of ICU admission, while controls received no early acetaminophen. The primary endpoint was in-hospital mortality. We implemented 1:1 propensity score matching (PSM) to minimize selection bias and balance baseline characteristics between cohorts. Multivariable Cox regression models adjusted for residual confounding.ResultsFrom 5,474 eligible patients, we generated balanced cohorts of 2,740 matched pairs. The acetaminophen group demonstrated significantly lower in-hospital mortality (11.4% vs 14.4%; adjusted HR 0.75, 95% CI 0.62–0.89, P = 0.001) compared to controls. This mortality reduction persisted consistently through sensitivity analyses and subgroup evaluations. Notably, early acetaminophen administration associated with improved survival metrics across multiple timepoints: ICU mortality (adjusted HR 0.63, 0.48–0.82; P = 0.001), 90-day mortality (adjusted HR 0.78, 0.66–0.92; P = 0.004), and 180-day mortality (adjusted HR 0.78, 0.67–0.92; P = 0.002). While no significant differences were observed in ICU or hospital length of stay between groups, early acetaminophen administration was linked to longer ICU-free days through day 28 (β = 0.71; P = 0.022) and longer vasopressor-free days through day 28 (β = 0.77; P = 0.012).ConclusionEarly acetaminophen administration demonstrates independent associations with reduced in-hospital mortality and improved secondary clinical outcomes in surgical ICU populations. These findings highlight the need for prospective trials to confirm therapeutic efficacy and establish causal inference for this readily available pharmacologic intervention.